SPE Annual Technical Conference and Exhibition 1992
DOI: 10.2118/24856-ms
|View full text |Cite
|
Sign up to set email alerts
|

Small, Highly Conductive Fractures Near Reservoir Fluid Contacts: Application to Prudhoe Bay

Abstract: The paper describes the techniques used in Prudhoe Bay to place small, highly conductive fractures in areas of the field where there is no fracture containment to prevent fracture growth into an aquifer.A reservoir study to investigate the effects of fracturing close to oil water contacts is presented, together with 3D fracture modelling of fractures with no downward containment. The paper highlights the importance of spurt losses in both frac designs and minifrac analyses, when fracturing high permeability re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Recent workover experience in the ~ 100 md "Zone 3" of the main Ivishak pay formation shows propped fractures definitely stimulating production from that zone, with fracture stimulations increasing field productivity by ;::;: 20% (more than 200,000 bopd). 3,4 However, with the underlying, high permeability (> 1000 md) "Zone 4" watered out, fracture penetration for Zone-3 is severely limited in many areas of the field to avoid fracturing into a watered out Zone-4.…”
Section: Figure 2 -Typical Cook Formation Log Section In Gullfaks Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent workover experience in the ~ 100 md "Zone 3" of the main Ivishak pay formation shows propped fractures definitely stimulating production from that zone, with fracture stimulations increasing field productivity by ;::;: 20% (more than 200,000 bopd). 3,4 However, with the underlying, high permeability (> 1000 md) "Zone 4" watered out, fracture penetration for Zone-3 is severely limited in many areas of the field to avoid fracturing into a watered out Zone-4.…”
Section: Figure 2 -Typical Cook Formation Log Section In Gullfaks Fieldmentioning
confidence: 99%
“…Such a indirect vertical fracture completion (IVFC) achieves several goals: I) First, the fracture stimulates production from lower penneability pay, increasing reserve recovery from that zone of the fonnation, 2) Second, connection is established to the high penneability zone of the formation, but production from the high penneability pay, through the fracture, is restricted, thus final production is more unifonnly distributed over the fonnation thickness, optimizing reservoir management, 3) Third, if the high penneability zone is prone to sand production, then the need for sand control is bypassed, often reducing completion costs. This can be of critical importance in areas (such as the North Sea) where seawater injection leads to severe scaling problems where scaling often totally plugs gravel pack wells quickly after WET.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Prats demonstrated that a propped fracture completion may be "viewed" as a completion with an increased effective wellbore radius (r w '). The fracture skin, Sr, is then defined as 492 Sf = -In(rw'/Lf) -In(Ltirw) ...... (2) where rw is the wellbore radius and Lris the fracture propped half-length. Values of rw'lLr are given as a function of the fracture conductivity ratio (FCD).l2 This is defined as…”
Section: Skin Analysis Of Fandp Completionsmentioning
confidence: 99%
“…If we do not desire a fracture to grow into unwanted water and/or gas zones and ifthere are no strong formation barriers to limit such a growth, the design of treatment volume and pump rate requires special attentions. 2 In this case, one may assume an uncontained (radial) fracture geometry with Lrbeing less than one half of the total desired height.…”
Section: Fracture Conductivity and Propped Length Requirementsmentioning
confidence: 99%
“…Once the fracture geometry and C L have been determined, further analytical techniques 3,4 are available for designing the correct TSO fracture stimulation. These analytical tools are of great benefit to the user when anticipated fracture dimensions are well understood [4][5][6] . In many instances, however, it is difficult to predict a fracture's geometry.…”
Section: Introductionmentioning
confidence: 99%